Analysis of the Nursing Effect of Anesthesia Care Integration Combined with Preventive Nursing on Older Patients with Lumbar Disc Herniation During the Perioperative Period - Liu H; Li P; Yu D; Ma Z; An Y; Li S; Cai L (Risk Management and Healthcare Policy, 2023)
Honghong Liu,1 Peng Li,1 Dan Yu,1 Zhongxi Ma,2 Yu An,1 Si Li,1 Lin Cai1 1Department of Anesthesiology, Wuhan Fourth Hospital, Wuhan, 430033, People’s Republic of China; 2Department of Spine Surgery, Wuhan Fourth Hospital, Wuhan, 430033, People’s Republic of ChinaCorrespondence: Lin Cai, Department of Anesthesiology, Wuhan Fourth Hospital, No. 473, Hanzheng Street, Qiaokou District, Wuhan, 430033, People’s Republic of China, Tel +86 17764059606, Email Yellow0707@163.comObjective: This study explored the nursing effect of anesthesia care integration combined with preventive nursing on older patients with perioperative lumbar disc herniation (LDH).Methods: Clinical data of 100 older patients with LDH who were admitted to our hospital between May 2017 and May 2022 were used, and there were no patients who had not had surgery between January and May 2020 because of the COVID-19 pandemic. Based on the different nursing methods, the patients were divided into control and observation groups, with 50 cases each. The control group received anesthesia care integration, whereas the observation group received anesthesia care integration combined with preventive nursing. Lumbar spine function, pain score, anesthesia recovery assessment, and nursing effects were compared between the two groups.Results: The scores of the anesthesia recovery assessment of the two groups were compared, and the vital signs of the observation group during recovery from anesthesia were significantly better than those of the control group (P< 0.05). After nursing care, the Japanese Orthopaedic Association (JOA) score of the observation group was significantly higher than that of the control group; however, the numerical scale (NRS) score of the observation group was significantly lower than that of the control group (P< 0.05). After nursing care, the physical comfort, emotional state, psychological support, self-care ability, and pain scores were higher in the observation group than in the control group; however, the NRS score of the observation group was significantly lower than that of the control group (P< 0.05).Conclusion: Anesthesia care integration combined with preventive nursing has a positive effect on older patients with perioperative LDH, and it significantly improves lumbar spine function, reduces pain, shortens recovery time, and benefits physical and mental health.Keywords: anesthesia nursing, preventive nursing, lumbar disc herniation, nursing effect, lumbar spine function